Iron and nickel isotope compositions of presolar silicon carbide grains from supernovae. (15th January 2018) - Kodolányi, János; Stephan, Thomas; Trappitsch, Reto; Hoppe, Peter; Pignatari, Marco; Davis, Andrew M.; Pellin, Michael J.
Abstract: We report the carbon, silicon, iron, and nickel isotope compositions of twenty-five presolar SiC grains of mostly supernova (SN) origin. The iron and nickel isotope compositions were measured with the new Chicago Instrument for Laser Ionization, CHILI, which allows the analysis of all iron and nickel isotopes without the isobaric interferences that plagued previous measurements with the NanoSIMS. Despite terrestrial iron and nickel contamination, significant isotopic anomalies in 54 Fe/ 56 Fe, 57 Fe/ 56 Fe, 60 Ni/ 58 Ni, 61 Ni/ 58 Ni, 62 Ni/ 58 Ni, and 64 Ni/ 58 Ni were detected in nine SN grains (of type X). Combined multi-isotope data of three grains with the largest nickel isotope anomalies (>100‰ or <−100‰ in at least one isotope ratio, when expressed as deviation from the solar value) are compared with the predictions of two SN models, one with and one without hydrogen ingestion in the He shell prior to SN explosion. One grain's carbon-silicon-iron-nickel isotope composition is consistent with the prediction of the model without hydrogen ingestion, whereas the other two grains' isotope anomalies could not be reproduced using either SN models. The discrepancies between the measured isotope compositions and model predictions may indicate element fractionation in the SN ejecta prior to or during grain condensation, and reiterate the need for three-dimensional SN models.